Revisiting crop and livestock integration in sheep and goat systems of Morocco: new insights - El Amiri B.; Nassif F. (Efficiency and resilience of forage resources and small ruminant production to cope with global challenges in Mediterranean areas, 2021)
Mixed farming with crops and livestock, particularly cereals associated with sheep rearing has been and still is the predominant farming system in Morocco. Because of the high diversity of topography, soils, climate, the extent of arable, rangelands, crop and livestock integration in sheep and goat systems takes a variety of forms. The integration depends on cultivated crops on-farm, available feed sources, breeds, and production objectives. Most studies on Moroccan sheep and goat systems adopt technicist approaches. The aim of this paper is to revisit the main sheep and goat production systems. It is based on specialised studies and field work on sheep and goats in the Middle-Atlas, Azilal and the plains of Settat and Khouribga provinces. The analysis focuses on the pastoral system of the eastern steppes as an example of the occurring shifts in sheep production. It is argued that the use of typologies hides the evolutionary processes underlying the production systems and the extent of diversity and interaction within systems. For a better understanding of croplivestock integration, multi-disciplinary approaches are necessary
1. Joint meeting of the FAO-CIHEAM Networks on Sheep and Goats (Subnetworks on Nutrition and Production Systems) and on Mediterranean Pastures, 2019/10/23-25, Meknes (Morocco)